Distance, production, virtual trade and growth: A note - Biswajit Mandal (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper argues that distance is not necessarily harmful to trade. It is shown that there may be an increase in the production and volume of trade if time zones of the trading nations are non-overlapping. This implies a positive effect of distance on the volume of trade in general and virtual trade in particular. It is also shown that exploitation of time zone differences raises welfare and ensures capital accumulation. The paper builds on the emerging literature on time zones and pure theory of international trade.
Keywords: F1; 330; Trade; time zone